Early social deficits in TgF344-AD rats are accompanied by sex-specific parvalbumin-positive interneuron reduction and altered brain oscillations in the hippocampal CA2 - Daniela Černotová; Karolína Hrůzová; Jan Touš; Radek Janča; Aleš Stuchlík; David Levčík; Jan Svoboda (Neurobiology of Disease)
Social withdrawal and deficits in social cognition are hallmarks of Alzheimer's disease (AD). While early deficits in social behavior and memory have been documented in mouse AD models, they remain understudied in rat models. Early-stage AD is accompanied by dysfunction of parvalbumin-positive (PV+) interneurons, implicating their potential connection to early symptoms. In this study, we employed a 5-trial social memory task to investigate early deficits in social cognition in 6-month-old TgF344-AD male and female rats. We counted the number of PV+ interneurons and recorded local field potentials during social interactions in the hippocampal CA2 – a region critical for social information processing. Our results show decreased social interest and novelty preference in TgF344-AD male and female rats. However, reduced PV+ interneuron numbers were observed only in female rats and specific to the CA2 area. The electrophysiological recordings revealed reduced theta-gamma phase-amplitude coupling in the CA2 during direct social interactions. We conclude that deficits in social cognition accompany early-stage AD in TgF344-AD rats and are potentially linked to PV+ interneuron and brain oscillatory dysfunction in the CA2 region of the hippocampus.